Effects of Causal Attribution and Implicit Mind-Set on Wisdom Development. (June 2020) - Alhosseini, Fatemeh; Ferrari, Michel
This study investigates the relationship between motivation and the development of wisdom. Eighty Canadian participants were interviewed and completed Ardelt's Three-Dimensional Wisdom Scale (3D-WS). Using a mixed method design, we assessed wisdom definitions, interpersonal causal attributions, and mind-set about developing wisdom. A chi-square analysis revealed a significant relationship between attribution and mind-set about wisdom development. Two multivariate analyses of variance showed that both factors significantly influenced wisdom scores on the 3D-WS. These results suggest that people who consider wisdom development to be controllable and believe that their personal wisdom can be developed (i.e., growth mind-set) tend to be wiser, regardless of their definition of wisdom. By introducing the importance of mind-set and attribution, this study will open new avenues for research on teaching for wisdom and allow educators to develop programs to cultivate wisdom that focus on altering attribution and mind-set.